New cassava products of future potential in India - Premkumar, T.; Padmaja, G.; Moorthy, S.N.; Nanda, S.K.; George, Mathew; Balagopalan, C. (International Center for Tropical Agriculture, 2001)
The Green Revolution and increasing living standards of the people of India, especially in Kerala, have resulted in a gradual shift in the cassava utilization pattern. Despite the fact that India has the world’s highest cassava yield, the crop’s importance for food security is giving way to its role as an industrial raw material. A well-organized grain distribution system and shifts to more remunerative plantation and horticultural crops also reduced the importance of cassava as a subsistence food crop in traditional farming systems in Kerala. In order to overcome this and retain cassava in the cropping system, concentrated efforts are being made to promote value-addition and find alternative uses. In the 1940s, cassava became an important raw material for the starch and sago industries established in Salem and Dharmapuri districts of Tamil Nadu. The cassava-based starch industry recorded a high rate of growth over the past five decades and has currently a turnover of 3000 million Indian rupees worth of starch and sago. The produce is marketed through a well-organized cooperative society, which is presently the largest agro-processing cooperative venture in South and East Asia. The sustainability of industrial growth of cassava depends to a large extent on diversification and value-addition, for increasing internal demand as well as export markets. Three and a half decades of research on cassava utilization at CTCRI has led to the development of several technologies for value addition and in situ utilization. The potential markets for products, such as pregelatinized instant and convenience foods, extruded and fermented food products, feed products using by-product utilization for poultry, and value-addition through microbial enrichment, modified starch products like adhesives, sweeteners, cold water-soluble starch, commodity chemicals like citric acid, ethanol, biodegradable polymers incorporating cassava starch, biogas from starch factory wastes, etc. are discussed in this paper. The future priorities and utilization strategies for cassava, comprising diversified products, setting up of rural agro-enterprises through the involvement of NGOs, by-product utilization as fish or poultry feed, biofertilizers from cassava starch factory waste and large commercial ventures like biodegradable plastics and alcohol are enumerated. The need for an effective technology transfer system to inform industrialists of the benefits of adopting root and tuber crop technologies is also highlighted.